CD30+ Cutaneous T Cell Lymphoma: Response to Rotational Total Skin Electron Irradiation. Issue 2 (June 2016) - Danish, Hasan; Heumann, Thatcher; Bradley, Kyle; Switchenko, Jeffrey; Esiashvili, Natia; Lechowicz, Mary; Flowers, Christopher; Khan, Mohammad
Abstract Introduction Rotational total skin electron irradiation (RTSEI) is an effective therapy for cutaneous T cell lymphoma (CTCL). CD30 expression has been identified as a prognostic factor in CTCL. Therefore, we investigated CD30 status, treatment response, and survival in our cohort of patients with CTCL treated with RTSEI. Methods Patients with CTCL treated with RTSEI (≥30 Gy) between 2000 and 2013 at our institution were identified, and clinical and pathologic data were retrospectively reviewed. Primary outcomes were complete clinical response (CCR; >90% reduction of skin disease burden), relapse-free survival (RFS), and overall survival (OS). Results Sixty-eight patients with CTCL treated with RTSEI were identified. Median age at diagnosis was 51 years with median follow-up of 61 months. Median OS was 76 months and median RFS was 11 months. Thirteen patients (19%) had CD30+ lymphocytes on initial pathology. In the CD30+ cohort, there were no T2, eight T3, and five T4 cases. In comparison, in the CD30− cohort, there were 18 T2, 29 T3, and 8 T4 cases (P  = 0.01). Six weeks post-RTSEI, CCR was 85% in CD30+ and 81% in CD30− cases (P  = 1). Six months post-RTSEI, CCR was 23% in CD30+ and 50% in CD30− cases (P  = 0.083). Conclusion RTSEI resulted in excellent CCR at 6 weeks in our cohort of patients with CTCL, with a median RFS of 11 months. We found CD30+ patients presented with significantly higher T stage at time of RTSEI and trended towards decreased CCR at 6 months post-RTSEI compared with the CD30− group.